Perilaku Merusak Diri pada Usia Dewasa Muda - Sambuaga, Michelle Christine; Akemat, Akemat; Wisnusakti, Khrisna; Mustikasari, Mustikasari; Imelisa, Rahmi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to explore the experiences of self-harm in young adulthood. The research employs a qualitative method with a phenomenological approach. The findings reveal three main themes in the experience of self-harm among young adults: 1) causes of self-harm, 2) ideas about self-harm, and 3) the cycle of self-harm. The conclusion indicates that the causes of self-harm vary among individuals, including factors such as family, academic, psychosocial, intrapersonal, personality, unpleasant past experiences, and physical health history. The ideas about self-harm among participants are influenced by everyday media exposure, such as social media and preferred films. The self-harm cycle begins with an individual's negative response to stressors, the type of self-harm performed, the negative feelings experienced before self-harm, and the relief felt as an emotional release after self-harm, which leads individuals to feel addicted and engage in repeated self-harm. In summary, self-harm is a maladaptive coping mechanism that provides only temporary relief from emotional burdens. Social skills training and counseling are recommended to reduce the risk of recurring behavior for those who are not yet ready to stop. Keywords: Self-Harm, Students, Young Adult